An Optimation on Iterative Weighing Coefficient of Three Dimensional Turbo Product Code - Zhao, Ning; Wang, Zhongyong; Jiang, Hua; Gong, Kexian; Sun, Peng; Wang, Wei (2021 7th International Conference on Computer and Communications (ICCC), 2021)
In this paper, we propose three categories of iterative decoding structures of three-dimensional(3-D) turbo product code(TPC), which is based on soft-input-soft-output(SISO) iterative decoding algorithm. Then by weighing the bit-error-rate(BER) curves of the 3-D TPC serial iterative decoder, a hybrid form of serial and parallel decoder and the parallel iterative decoder, and an optimal iterative decoding scheme is emerged. Furthermore, via adjusting the iterative weighing coefficient of the extrinsic information and equilibrating the proportion between the extrinsic information and the received information while decoding, the soft information of each bit is continuously modified to increase its reliability, delivering better decoding performance. Moreover, based on the enhanced structure of the 3-D TPC parallel iterative algorithm, we test different kinds of combinations of weighing coefficient, and pick out the best choice to achieve the lowest BER. Simulation results show that the performance of the modified 3-D TPC parallel decoder is substantially augmented under the circumstance of 3dB signal noise ratio(SNR) and 0.706 code rate, where the BER is quite close to the Shannon limit. under where its BER is almost approaching 10 −6 , which meets the BER requirements in modern wireless communication systems.